The microbiome of the habitat‐forming brown alga Fucus vesiculosus (Phaeophyceae) has similar cross‐Atlantic structure that reflects past and present drivers 1 - Capistrant‐Fossa, Kyle A. (2021)
Latitudinal diversity gradients have provided many insights into species differentiation and community processes. In the well-studied intertidal zone, however, little is known about latitudinal diversity in microbiomes associated with habitat-forming hosts. We investigated microbiomes of Fucus vesiculosus because of deep understanding of this model system and its latitudinally large, cross-Atlantic range. Given multiple effects of photoperiod, we predicted that cross-Atlantic microbiomes of the Fucus microbiome would be similar at similar latitudes and correlate with environmental factors. We found that community structure and individual amplicon sequencing variants (ASVs) showed distinctive latitudinal distributions, but alpha diversity did not. Latitudinal differentiation was mostly driven by ASVs that were more abundant in cold temperate to subarctic (e.g., Granulosicoccus_t3260, Burkholderia/Caballeronia/Paraburkholderia_t8371) or warm temperate (Pleurocapsa_t10392) latitudes. Their latitudinal distributions correlated with different humidity, tidal heights, and air/sea temperatures, but rarely with irradiance or photoperiod. Many ASVs in potentially symbiotic genera displayed novel phylogenetic biodiversity with differential distributions among tissues and regions, including closely related ASVs with differing north-south distributions that correlated with Fucus phylogeography. An apparent southern range contraction of F. vesiculosus in the NW Atlantic on the North Carolina coast mimics that recently observed in the NE Atlantic. We suggest cross-Atlantic microbial structure of F. vesiculosus is related to a combination of past (glacial-cycle) and contemporary environmental drivers.